The Impact of COVID-19 and the Challenges of Post-COVID Rehabilitation in a Developing Country - Uddin, Taslim; Rahim, Hasna Raihan; Khandaker, Md Nuruzzaman (Frontiers in Rehabilitation Sciences, 2022)
Coronavirus disease 2019 and the impact of COVID-19 on human functioning is gaining increased interest. Like many other lower-income countries, the Bangladesh health and rehabilitation sector was adversely affected by the COVID-19 and long covid disease. Multiple challenges were identified for preparedness and medical rehabilitation during COVID-19 surges. Appropriate supervision of multispecialty long COVID clinics and attention to rehabilitation team work is important. Rehabilitation plays a key role in the management of patients with COVID-19 and can reduce the length of hospital stay and improve health outcomes. While waiting for people to be fully vaccinated; ensuring equitable access to COVID-19 vaccination, health care, and rehabilitation services among people with disabilities should be a part of the core mission during the pandemic. All level of care including, critical , post- acute or long covid clinics scale up of rehabilitation services are needed. A physiatrist-led rehabilitation team approach is vital for the adaptation of rehabilitation interventions to improve the functional outcomes of persons with impairment and disability affected by COVID-19.